2023
DOI: 10.1186/s12967-023-04283-4
|View full text |Cite
|
Sign up to set email alerts
|

Randomized, double-blind, placebo-controlled study to evaluate the effect of treatment with an SPMs-enriched oil on chronic pain and inflammation, functionality, and quality of life in patients with symptomatic knee osteoarthritis: GAUDI study

Abstract: Background Specialized pro-resolving mediators (SPMs), including 18-HEPE, 17-HDHA, and 14-HDHA are recognized as potentially therapeutic in inflammatory diseases because SPMs regulate the inflammation process, which leads to, for example; swelling and the sensation of pain. In osteoarthritis (OA), chronic pain is described as the symptom that reduces patients´ quality of life (QoL). The GAUDI study evaluated the efficacy of SPMs supplementation in reducing pain in the symptomatic knee of OA pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…RvD3 was reduced in the serum of rheumatoid arthritis patients [56]. Furthermore, in line with the increased levels of SPMs in circulation, a recent randomized clinical study by Möller et al revealed that oral supplementation of marine oils led to reduced pain in individuals with symptomatic knee arthritis when compared to a placebo group [57]. Also, RvD1 was significantly reduced in vulnerable regions of atherosclerotic plaques [58].…”
Section: Discussionmentioning
confidence: 91%
“…RvD3 was reduced in the serum of rheumatoid arthritis patients [56]. Furthermore, in line with the increased levels of SPMs in circulation, a recent randomized clinical study by Möller et al revealed that oral supplementation of marine oils led to reduced pain in individuals with symptomatic knee arthritis when compared to a placebo group [57]. Also, RvD1 was significantly reduced in vulnerable regions of atherosclerotic plaques [58].…”
Section: Discussionmentioning
confidence: 91%
“…This approach was inspired from the current understanding of inflammation as a biphasic process of initiation and active resolution, [1] the latter being essentially regulated by lipid mediators with pro-resolving activity. [2d] While there is still some debate as to whether tri-hydroxylated SPMs in particular are produced in sufficient quantities to elicit a physiological response, [15] there is also strong evidence from animal studies that excess SPMs (e.g., upon injection) are highly effective in alleviating inflammation, [2d, 13] and initial clinical trials on SPM analogs [59] or SPM precursors [60] support anti-inflammatory and/or analgesic activity. As a result, the challenge for small molecule inflammation-resolving drugs is not only to increase SPM levels, but to increase them sufficiently to produce a pronounced and long-lasting effect.…”
Section: Discussionmentioning
confidence: 99%
“…SPMs reduce pro-inflammatory immune cells, increase the production of anti-inflammatory mediators, and counter-regulate pro-inflammatory mediators [ 56 ]. At the cellular level, this occurs through macrophage phagocytosis of pathogens, apoptotic cells, and cellular debris, and limits the infiltration of neutrophils and reduces chemokine and cytokine mediators to promote tissue repair and regeneration.…”
Section: Fatty Acidsmentioning
confidence: 99%